Humidity switching properties of sensors based on multiwalled carbon nanotubes/polyvinyl alcohol composite films. Issue 1 (17th August 2013) - Fei, Teng; Jiang, Kai; Jiang, Fan; Mu, Ren; Zhang, Tong
ABSTRACT Multiwalled carbon nanotubes (CNTs) were used as the conductive filler of composites for switching type humidity sensor. The CNTs were oxidized by mixed acids (H2SO4 : HNO3) at a mild temperature to modify carboxylic acid (COOH) groups on the surface of the nanotubes. The dispersibility of acid treated CNTs (CNTs‐COOH) in water is much improved, which is beneficial for dispersing CNTs in the polyvinyl alcohol (PVA) matrix without external additives. The obtained CNTs‐COOH/PVA sensors show nonlinear response to relative humidity (RH), that is, switching properties. The resistances of the sensors remain constant before 80% relative humidity (RH) and then increase sharply with RH, indicating excellent switching characteristic of the sensors. The 10 wt % CNTs‐COOH/PVA sensor shows a sensitivity (ΔR/Ro) of 32.3 at 100% RH. The humidity switching properties of CNTs‐COOH/PVA are much better than that of pristine CNTs/PVA. The improvements are attributed to the improved balance between the dispersibility of CNTs‐COOH and electrical conductivity of the composite films. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39726.